Optimization, Kinetics and thermodynamic modeling of pulp production from plantain stem using the kraft process - Effi Evelyn; Akindele Oyetunde Okewale; Chiedu Ngozi Owabor (Cleaner Chemical Engineering)
Pulp production is a very essential industrial process. This study employed response surface methodology (RSM) with a central composite design of experiment (CCD) to determine the best process conditions for kraft pulp production from plantain stems. The pulp pseudo-stem was physically pretreated by shredding, drying, grinding, and sieving. Kraft pulping was conducted using the CCD of the experiment and the process was optimized using RSM. The independent variables include the mass ratio of Sodium Hydroxide to Sodium Sulphide, temperature, and time, while the response is the pulp yield. The analysis of variance showed that the temperature, time, and ratio of NaOH to Na2S were significant. The obtained coefficient of determination (R²) value is 0.9125, which indicates a strong correlation is consistent with the adjusted (R²) value of 0.964. Optimum temperature, time, and NaOH: Na2S ratio values obtained at optimum were 110.50 C, 146.88 min, and 3.372. The yield of pulp obtained at this optimum process variable is 55.064 wt%. The mechanistic and thermodynamics results showed that at a higher model fit R2 value of 0.9977, rate constant of 6.3 × 10–3min-1, and lower activation energy value of 29.523 KJ/kg confirmed that the pseudo-first-order best described the kinetics of the pulp production process compared to the pseudo-second-order kinetics with activation energy value of 40.997 KJ/kg at R2 =0.9834. From this study, optimization of the process helps to maximize the Pulp yield while minimizing the resource consumption which in turn will also help to reduce the cost of production.